HITRAN Application Programming Interface (HAPI): A comprehensive approach to working with spectroscopic data. (July 2016) - Kochanov, R.V.; Gordon, I.E.; Rothman, L.S.; Wcisło, P.; Hill, C.; Wilzewski, J.S.
Abstract: The HITRAN Application Programming Interface (HAPI) is presented. HAPI is a free Python library, which extends the capabilities of the HITRAN online interface (www.hitran.org ) and can be used to filter and process the structured spectroscopic data. HAPI incorporates a set of tools for spectra simulation accounting for the temperature, pressure, optical path length, and instrument properties. HAPI is aimed to facilitate the spectroscopic data analysis and the spectra simulation based on the line-by-line data, such as from the HITRAN database [JQSRT (2013) 130, 4–50], allowing the usage of the non-Voigt line profile parameters, custom temperature and pressure dependences, and partition sums. The HAPI functions allow the user to control the spectra simulation and data filtering process via a set of the function parameters. HAPI can be obtained at its homepagewww.hitran.org/hapi . Highlights: HAPI extends the HITRAN online portal and provides an access to the HITRAN data. Free, flexible, and portable Python library for working with the spectroscopic data. Incorporates functions for querying, filtering and processing the spectroscopic data. Provides functionality for single-layer spectra simulation. Can be used in the radiative transfer codes, spectroscopic data validation, etc.